Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
[tex]x^2-2x-43=5 \\
x^2-2x+1-1-43=5 \\
(x-1)^2-44=5 \\
(x-1)^2=49 \\
\sqrt{(x-1)^2}=\sqrt{49} \\
|x-1|=7 \\
x-1=7 \ \lor \ x-1=-7 \\
x=8 \ \lor \ x=-6 \\
\boxed{x=-6 \hbox{ or } x=8}[/tex]
x² - 2x - 43 = 5
- 5 - 5
x² - 2x - 48 = 0
x = -(-2) +/- √((-2)² - 4(1)(-48))
2(1)
x = 2 +/- √(4 + 192)
2
x = 2 +/- √(196)
2
x = 2 +/- 14
2
x = 1 +/- 7
x = 1 + 7 ∨ x = 1 - 7
x = 8 ∨ x = -6
- 5 - 5
x² - 2x - 48 = 0
x = -(-2) +/- √((-2)² - 4(1)(-48))
2(1)
x = 2 +/- √(4 + 192)
2
x = 2 +/- √(196)
2
x = 2 +/- 14
2
x = 1 +/- 7
x = 1 + 7 ∨ x = 1 - 7
x = 8 ∨ x = -6
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.